Essential oils in the treatment of dermatozoonoses – a literature review (Research, Society and Development, 2021)
The indiscriminate use of medications has represented one of the greatest threats to Unique Health, given its role in antimicrobial resistance and its impacts on the environment. Thus, essential oils, substances with various therapeutic activities, are sought as a sustainable alternative to these drugs, highlighting their effectiveness in the treatment of dermatopathies of zoonotic origin, such as canine scabies, sporotrichosis, dermatophytosis and American tegumentary leishmaniasis. The present work aims to carry out a literature review on the use of essential oils in veterinary medicine, highlighting the treatment of dermatopathies of zoonotic origin. The acaricide, fungicidal and fungistatic effect of essential oils from Melaleuca alternifolia, Cedrus deodara, Azadirachta indica, Myrtus communis, Thymus vulgaris, Rosmarinus officinalis, Lavandula angustifolia, Cinnamomum cassia, Eugenia uniflora and Plectranthus amboinicus was demonstrated. Dermatozoonosis is increasingly resistant to commercial antifungals and antibiotics, and the use of alternative therapies using essential oils is relevant in order to alleviate this resistance and improve the health of animals. Therefore, among the evaluated studies, it is demonstrated that the essential oils of Melaleuca alternifolia, Cedrus deodara, Azadirachta indica, Myrtus communis, Thymus vulgaris, Rosmarinus officinalis, Lavandula angustifolia, Cinnamomum cassia, Eugenia uniflora and Plectranthus amboinicus present satisfactory therapeutic results in vitro of clinically important dermatozoonoses, however, it is necessary to carry out in vivo studies to verify the effectiveness of these compounds, monitoring their action through physiological barriers and metabolism of animals.